Velocity distribution description in a sand bed branching channel with different angles and bed widths - Alomari, Nashwan K.; Yusuf, Badronnisa; Mohammed, Thamer Ahmed; Ghazali, Abdul Halim (UNIV LAGOS, 2016)
A branching flow is a hydraulic phenomenon presents in many rivers or manmade channels and has many practical hydraulic engineering applications such as in irrigation systems where water is diverted from a river to irrigation canals. A sand bed physical model was used in this study to investigate the velocity distribution at the branching channel junction. Different cases of the branch channel geometry represented by three branch channel angles (30 ̊, 60 ̊, and 90 ̊) and three branch channel width ratios (30%, 40%, and 50%) were examined to characterize the velocity distribution. Experimental work finding displays a low velocity region in the upstream side of the beginning of the branch channel occurred in all cases of the branch channel geometry. Branch channel with 60 ̊ angle recorded the maximum low velocity region length, then 90 ̊ branching angle, and the minimum length took place at 30 ̊ angle. Moreover, 30 ̊ branching angle recorded the lees different of the velocity values between upstream and downstream sides of the branch channel and the less flow impact on the downstream branch channel side wall.